An Inexpensive and Recyclable Silver‐Foil Catalyst for the Cyclopropanation of Alkenes with Diazoacetates under Mechanochemical Conditions. Issue 38 (14th September 2015) - Chen, Longrui; Bovee, Mark O.; Lemma, Betsegaw E.; Keithley, Kimberlee S. M.; Pilson, Sara L.; Coleman, Michael G.; Mack, James
Abstract The diastereoselective cyclopropanation of various alkenes with diazoacetate derivatives can be achieved under mechanochemical conditions using metallic silver foil and a stainless‐steel vial and ball system. This solvent‐free method displays analogous reactivity and selectivity to solution‐phase reactions without the need for slow diazoacetate addition or an inert atmosphere. The heterogeneous silver‐foil catalyst system is easily recyclable without any appreciable loss of activity or selectivity being observed. The cyclopropanation products were obtained with excellent diastereoselectivities (up to 98:2 d.r.) and in high yields (up to 96 %).